The global multi-hub conference: Inclusion, sustainability, and academic politics - Richard Parncutt (Sustainable Futures, 2025)
Single-location international academic conferences are neither inclusive nor sustainable. The per-capita emissions are comparable with the global-average annual personal carbon footprint. Colleagues who cannot afford travel, accommodation, and registration are excluded. A multi-hub conference is open to colleagues from almost anywhere while at the same time enabling deep cuts in emissions and maintaining constant face-to-face contact within hubs. To achieve that, existing regional conferences on different continents can be held simultaneously and electronically linked. All hubs can be treated equally. Real-time interaction can be maximized by locating three hubs exactly eight hours apart (e.g., London, Tokyo, Los Angeles) with other hubs in nearby time-zones, and limiting the working day at each hub to three successive four-hour slots (morning, siesta, evening). With a hub on each inhabited continent, the conference becomes globally inclusive; for many academic subdisciplines, the optimal number of hubs may be seven (two in Asia). The necessary equipment is available in most university teaching rooms: laptop with inbuilt camera and microphone, videoconferencing software, data projector, loudspeaker. Multi-hub conferences are consistent with the no-harm principle: research should not harm people, animals, or the environment. This paper offers conference organizers useful background information on the logistics of multi-hub conference organization, the ethics of academic conferencing, and the politics of radical change in democratic committees.